E-commerce logistics workers: subalternity or vanguard of the workers’ movement in platform capitalism. The case of the Rotterdam port region - López Calle, Pablo; Roiz Ceballos, Elías (Cuadernos de Relaciones Laborales, 2026)
In this text we study the forms of collective bargaining in the e-commerce logistics sector in the Netherlands, taken as an analyzer of the possibilities and limits of the new forms of resistance in the so-called platform capitalism. We identify three characteristic forms of articulation of labor relations after the mutation of traditional bargaining models based on the establishment of norms of general effectiveness through representative class unions: the model of certifications; the judicialization of labor relations; and direct action. These different bargaining repertoires correspond to different positions in the production process, together with the different ethnic-migrant condition of the employees. This division has led to a continuous loss of standards of conditions for the whole. Finally, possible ways of rearticulating collective action to reverse this process are proposed.